Cochlear Implantation in the Elderly: Does Age Matter?. Issue 1 (January 2017) - Rohloff, Katharina; Koopmann, Mario; Weiß, Daniel; Rudack, Claudia; Savvas, Eleftherios
Abstract : Objective: To compare the outcome of hearing rehabilitation in younger versus older adult cochlear implant recipients. Analysis of surgical and postoperative complications, as well as the number of auditory therapy sessions in the two age groups. Study Design: Individual retrospective cohort study. Methods: A cohort of 145 postlingually deafened adults was evaluated in this study. The patients were divided into two age groups based on the age at implantation: Group I, 18 to 69 years; and Group II, 70 and older. Postoperative hearing performance was measured based on the German Freiburg monosyllabic word test (FM) and the Oldenburg sentence test (OLSA). Results: Postoperative hearing evaluation results in both groups plateaued and remained constant after 12 months of implantation. The results remained constant at the 2 and 3-year time intervals. There was a significant difference in complications arising after cochlear implantation. Group II showed more cases of vertigo and dysgeusia. The number of auditory therapy sessions in both groups was similar. Conclusion: Cochlear implantation in the elderly is highly effective; the postoperative hearing performance is at the same level as younger adult recipients. Complex hearing tasks, such as hearing in background noise, requires an equally long time for comprehension. The recovery period of vestibular dysfunction after surgery may be longer in the elderly. Auditory therapy rehabilitation is not more time consuming in the elderly compared with the younger counterparts.